Ciliary neurotrophic factor signaling in the rat orbitofrontal cortex ameliorates stress-induced deficits in reversal learning - Girotti, Milena (Neuropharmacology, 2019)
Deficits in cognitive flexibility, i.e. the ability to modify behavior in response to changes in the environment, are present in several psychiatric disorders and are often refractory to treatment. However, improving treatment response has been hindered by a lack of understanding of the neurobiology of cognitive flexibility. Using a rat model of chronic stress (chronic intermittent cold stress, CIC) that produces selective deficits in reversal learning, a form of cognitive flexibility dependent on orbitofrontal cortex (OFC) function, we have previously shown that JAK2 signaling is required for optimal reversal learning. In this study we explore the molecular basis of those effects. We show that, within the OFC, CIC stress reduces the levels of phosphorylated JAK2 and of ciliary neurotrophic factor (CNTF), a promoter of neuronal survival and an activator of JAK2 signaling, and that neutralizing endogenous CNTF with an intra-OFC microinjection of a specific antibody is sufficient to produce reversal-learning deficits similar to stress. Intra-OFC delivery of recombinant CNTF to CIC-stressed rats, at a dose that induces JAK2 and Akt but not STAT3 or ERK, ameliorates reversal-learning deficits, and Akt blockade prevents the positive effects of CNTF. Further analysis revealed that CNTF may exert its beneficial effects by inhibiting GSK3β, a substrate of Akt and a regulator of protein degradation. We also revealed a novel mechanism of CNTF action through modulation of p38/Mnk1/eIF4E signaling. This cascade controls translation of select mRNAs, including those encoding several plasticity-related proteins. Thus, we suggest that CNTF-driven JAK2 signaling corrects stress-induced reversal learning deficits by modulating the steady-state levels of plasticity-related proteins in the OFC.